2022
DOI: 10.1101/2022.05.03.490470
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Critical Mechanistic Features of HIV-1 Viral Capsid Assembly

Abstract: The maturation of HIV-1 capsid protein (CA) into a cone-shaped lattice encasing the condensed RNA genome is critical for viral infectivity. CA can self-assemble into a wide range of capsid morphologies made of ~175-250 hexamers and exactly 12 pentamers. Most recently, cellular polyanion inositol hexakisphosphate (IP6) has been demonstrated to facilitate conical capsid formation by coordinating a ring of arginine residues within the central cavity of capsid hexamers and pentamers. However, the precise interplay… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…A recent molecular dynamics simulation analysis of capsid assembly (50) lends further support to this model, suggesting that IP6 has a higher affinity for pentameric CA than for hexameric CA within capsids and that IP6 is critical for assembly of a high-curvature lattice.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…A recent molecular dynamics simulation analysis of capsid assembly (50) lends further support to this model, suggesting that IP6 has a higher affinity for pentameric CA than for hexameric CA within capsids and that IP6 is critical for assembly of a high-curvature lattice.…”
Section: Discussionmentioning
confidence: 81%
“…A recent molecular dynamics simulation analysis of capsid assembly (50) lends further support to this model, suggesting that IP6 has a higher affinity for pentameric CA than for hexameric CA within capsids and that IP6 is critical for assembly of a high-curvature lattice. Moreover, a cryo-ET analysis (23) of capsid cores from native virions reported that the central pores of viral pentamers contained two strong densities that were predicted to be IP6.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…303,304 It must be noted that the UCG approach has already achieved notable success in treating realistic and highly complex biomolecular systems, an example of which is the assembly of the HIV-1 virus capsid from the more than 1,000 copies of its capsid (CA) protein component. 81,84,305 4-3. Structural Representability.…”
Section: -2a Slow State Transition Limitmentioning
confidence: 99%
“…299,300 In a coarser description (lower resolution), UCG models based largely on the SST limit have been applied to capture the dynamic self-assembly behavior originating from many-protein HIV viral capsids. 81,84,305 As such, when conformational transitions in complex biomolecules rarely occur, the SST limit can effectively embed the finely detailed chemical nature into a reduced level of representation.…”
Section: -2a Slow State Transition Limitmentioning
confidence: 99%